GaAs PHEMT PERFORMANCE INCREASE USING DELTA-DOPING IN THE FORM OF NANOWIRES OF TIN ATOMS - A. E. Yachmenev; V. I. Ryzhii; P. P. Maltsev (Российский технологический журнал)
The PHEMT epitaxial structures with a doping profile in the form of tin nanowires were fabricated using vicinal GaAs substrate disoriented by 0.3° in relation to accurate orientation (100). Investigation of electron transport properties of the structures with nanowires of tin atoms on vicinal GaAs substrates have been presented. It was determined that non-optimal growth temperature of cap layers leads to degradation of electrophysical parameters of the samples and prevent forming of tin one-dimensional channels. Anisotropy of the saturation current on current-voltage characteristics was obtained when current flow along and across nanowires. Field effect transistors with special topology for orthogonal current flow were fabricated and frequency characteristics were measured. The evident anisotropy of the frequency characteristics for PHEMT was shown. Gain coefficient MSG (Maximum Stable Gain) of the fabricated PHEMT for current flow along nanowires correlates to best-achieved values of MSG for GaAs PHEMT.